Effect of Sodium Butyrate Supplementation in Growth Performance of Nile Tilapia (Oreochromis sp.) - Nurul Fatimah; Huda Verdian, Aldi; Rio Yudufi Subhan; Linuwih Aluh Prastiti; Arif Faisal Siburian (University of PGRI Palembang, 2024)
Cultivation of Nile tilapia (Oreochromis sp.) often encounters challenges, particularly in intensive farming systems, where low feed efficiency adversely affects growth performance. Therefore, solutions to enhance both growth and feed efficiency are required. One promising approach is the supplementation of butyric acid in feed. The benefits of butyric acid supplementation on growth performance and gut health in mammals and poultry have been well-documented. However, information on its effects on Nile tilapia remains limited. This study aimed to evaluate the effects and determine the optimal dose of a microencapsulated sodium butyrate (30%) product on the production performance of Nile tilapia. The experiment was conducted over 75 days to assess production performance parameters. Feeding was carried out three times daily at 3-5% of body weight per day with commercial feed containing 25-30% protein. Sodium butyrate (30%) was added to the feed in the treatment ponds at doses of 0% (0 g/kg feed), 0.1% (1 g/kg feed), 0.2% (2 g/kg feed), and 0.3% (3 g/kg feed), with additional oil used as a binder. The results showed that supplementation of 30% sodium butyrate to the feed improved the growth performance of Nile tilapia, with the best results observed at a dose of 2 g/kg feed. Budidaya ikan nila (Oreochromis sp.) kerap menghadapi tantangan, terutama dalam sistem pemeliharaan intensif, di mana efisiensi pakan yang rendah berdampak negatif pada pertumbuhan ikan. Oleh karena itu, diperlukan solusi untuk meningkatkan pertumbuhan dan efisiensi pakan. Salah satu pendekatan yang dapat dilakukan adalah suplementasi asam butirat dalam pakan. Manfaat suplementasi asam butirat terhadap kinerja pertumbuhan dan kesehatan saluran pencernaan pada mamalia dan unggas telah banyak dilaporkan. Namun, informasi mengenai efeknya pada ikan nila masih terbatas. Penelitian ini bertujuan untuk mengevaluasi efek dan menentukan dosis optimal produk sodium butirat mikroenkapsulasi (30%) terhadap kinerja pertumbuhan ikan nila. Percobaan dilakukan selama 75 hari untuk mengukur parameter kinerja produksi. Pakan diberikan tiga kali sehari sebanyak 3-5% dari bobot tubuh per hari menggunakan pakan komersial dengan kandungan protein 25-30%. Sodium butirat (30%) ditambahkan ke pakan pada kolam perlakuan dengan dosis 0% (0 g/kg pakan), 0,1% (1 g/kg pakan), 0,2% (2 g/kg pakan), dan 0,3% (3 g/kg pakan), dengan tambahan minyak sebagai perekat. Hasil penelitian menunjukkan bahwa suplementasi sodium butirat (30%) dalam pakan meningkatkan kinerja pertumbuhan ikan nila, dengan hasil terbaik diperoleh pada dosis 2 g/kg pakan.